2017
DOI: 10.1038/ncomms14830
|View full text |Cite
|
Sign up to set email alerts
|

Src family kinases Fyn and Lyn are constitutively activated and mediate plasmacytoid dendritic cell responses

Abstract: Plasmacytoid dendritic cells (pDC) are type I interferon-producing cells with critical functions in a number of human illnesses; however, their molecular regulation is incompletely understood. Here we show the role of Src family kinases (SFK) in mouse and human pDCs. pDCs express Fyn and Lyn and their activating residues are phosphorylated both before and after Toll-like receptor (TLR) stimulation. Fyn or Lyn genetic ablation as well as treatment with SFK inhibitors ablate pDC (but not conventional DC) respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…Especially, we show that LYN, a member of SFK, is involved in the pathogenesis of AD by regulating an oAb 1-42 -FcgRIIb2-SHIP2 pathway in neuronal cells, listing LYN as a neuropathogenic factor in AD. FYN, a member of SFK, is highly homologous to LYN, and much of its function overlaps with LYN in that functional complementation is attained by FYN to mediate allergic responses and plasmacytoid dendritic cell responses in LYN-deficient cells and mice (38,39). As members of SFK share a common regulatory mechanism that determines the phosphorylation status of the Cterminal regulatory domain, it is plausible that both LYN and FYN are activated by oAb under same process (40).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, we show that LYN, a member of SFK, is involved in the pathogenesis of AD by regulating an oAb 1-42 -FcgRIIb2-SHIP2 pathway in neuronal cells, listing LYN as a neuropathogenic factor in AD. FYN, a member of SFK, is highly homologous to LYN, and much of its function overlaps with LYN in that functional complementation is attained by FYN to mediate allergic responses and plasmacytoid dendritic cell responses in LYN-deficient cells and mice (38,39). As members of SFK share a common regulatory mechanism that determines the phosphorylation status of the Cterminal regulatory domain, it is plausible that both LYN and FYN are activated by oAb under same process (40).…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins detected, LYN, a member of Src family kinases (SFK), has been shown its function in the maturation of DC and pDC response 36,37 . Immunoprecipitation confirmed that LYN interacted with STING after DMXAA stimulation in WT BMDC while LYN constitutively interacted with STING in the Fcgr2b-deficient BMDC (Fig.…”
Section: Sting Mediated Maturation Of Conventional DC and Differentiamentioning
confidence: 99%
“…Lyn kinase regulates DC maturation, and genetic deletion of Lyn ablates pDC 36,37 . We hypothesized that STING promoted DC maturation and pDC differentiation through LYN signaling pathway, and the inhibition of LYN should affect the STING-induced BMDC differentiation.…”
Section: Sting Mediated Maturation Of Conventional DC and Differentiamentioning
confidence: 99%
See 2 more Smart Citations